Montesquieu and the despotic ideas of Europe : an interpretation of the Spirit of the laws - Sullivan, Vickie B. (The University of Chicago Press, 2017)
Montesquieu's Spirit of the Laws is famous for overtly associating despotism with Asia and the Middle East and not with Europe. A scholar on this basis might be inclined to term Montesquieu an Orientalist, one who gazes at exotic foreign cultures in order to exert control over these distant peoples in both thought and in reality. Sullivan argues, however, that Montesquieu's great work, contrary to first impressions, actually implicates Europe itself with despotism. Specifically, the Frenchman reveals that many of Europe's greatest philosophical and religious ideas are themselves despotic and have inspired cruel and violent practices on the continent and beyond. Indeed, when Montesquieu uses the formulation "idées despotiques" in the work, he refers to the deplorable punishments that such ideas inspire. In some cases, hoary philosophical authorities such as Plato and Aristotle articulate and advocate for such ideas. Remaining ensconced in revered sources, they can wait for centuries to be rediscovered and revived. In other cases, Christians have promulgated ideas that induce human beings to commit earthly outrages for the sake of heavenly salvation. More recently, Machiavelli and Hobbes have introduced terrifying abuses in their attempts to correct those of their predecessors. These despotic ideas possess both longevity and geographical range, and therefore remain a constant threat. Montesquieu seeks to foster in the readers of his masterwork a repugnance for these despotic ideas so that future generations might be relieved of their vicious influence.